The Effectiveness of Virtual State Defense Preparedness Learning during the Covid-19 Pandemic in Increasing the Nationalism of State Civil Apparatus (ASN) in Basic Education for CPNS Group III Batch 2 in Tanjabbar Regency in 2020 - Fianita Dhany (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2020)
The covid-19 pandemic has brought big changes to the world, including Indonesia. The policies issued by the government to limit the spread of the coronavirus have an impact on various fields around the world, especially on education. Learning that should be done face-to-face turns into virtual learning, this very changing learning system has a big impact on the implementation of CPNS basic education training, virtual learning, especially on the first agenda, namely the Defense Preparedness course which aims to shape the character of CPNS to behave and act professionally, behave with quality performance, ethics based on national values, and high commitment to face changes in the strategic environment of work units/organizations as a real manifestation of the spirit of defending the State of a civil servant. This rationale makes state defence preparedness one of the most important training courses in CPNS basic training (Latsar). The characteristics of the effectiveness of the learning program are that they are successful in bringing participants to the learning objectives and indicators of success that have been determined and providing an attractive learning experience. In the state defence preparedness training, the author is interested in conducting an analysis related to the effectiveness of the implementation of learning in the State Defense Preparedness training in fostering a virtual sense of nationalism from the participant's point of view in receiving state defence preparedness learning to increase the sense of nationalism of CPNS Ditsar participants, especially CPNS Training Participants. Tanjabbar Force.2 in 2020 with a total of 34 people. This study used a survey method which was conducted online. The data was collected by distributing questionnaires online to 34 respondents as a sample. The results of the data obtained showed that the implementation of virtual learning was carried out effectively 70.6% of the implementation was effective.